2017
DOI: 10.1038/s41598-017-01313-2
|View full text |Cite
|
Sign up to set email alerts
|

Accessible areas in ecological niche comparisons of invasive species: Recognized but still overlooked

Abstract: Understanding biological invasions is crucial for their control and prevention. Specially, establishing whether invasive species operate within the constraint of conservative ecological niches, or if niche shifts occur at all commonly as part of the invasion process, is indispensable to identifying and anticipating potential areas of invasion. Ecological niche modeling (ENM) has been used to address such questions, but improvements and debate in study design, model evaluation, and methods are still needed to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 62 publications
1
43
0
3
Order By: Relevance
“…3B). This imbalance between sensitivity and specificity of the occurrence-based SDM (Table 2) can also be interpreted as its inferior transferability or lack of generality (Qiao et al 2017, Yen et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…3B). This imbalance between sensitivity and specificity of the occurrence-based SDM (Table 2) can also be interpreted as its inferior transferability or lack of generality (Qiao et al 2017, Yen et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Following the recommendations of Broennimann et al (2012) and Petitpierre et al (2017), we calibrated a principal components analysis (PCA) on this global background and used the first two PC axes (containing 84.39% of the variation) as a common climate space. Given that many pines are native to the Northern Hemisphere but naturalized in the Southern Hemisphere, we also plotted the climate of each hemisphere to assess the potential for systematic differences that could influence interpretation of our niche models (Qiao, Escobar, & Peterson, 2017).…”
Section: Niche Modellingmentioning
confidence: 99%
“…They are included in disciplines as diverse as conservation biology, historical biogeography, evolution, and community ecology (Dennis and Stefan 2009, McCormack et al 2010, Pellissier et al 2013, Guisan et al 2014, all of them rely on interpreting patterns and drivers of species' distributions across landscapes. Despite widespread interest and application, the field remains young and has yet to coalesce on lexicon, methods, and theory (Elton 1927, Jackson and Overpeck 2000, Soberón and Nakamura 2009, Guisan et al 2014, Qiao et al 2017. One limitation faced by many comparative niche studies stems from the fact that niche similarity is often quantified in geographic space (Warren et al 2008(Warren et al , 2010 as opposed to environmental-space , Di Cola et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Petitpierre et al (2012) demonstrated the importance of quantifying analog climates when comparing niche shifts among terrestrial plant invaders. Qiao et al (2017) directly addressed non-equilibrium nature of species' distributions by restricting statistical analyses to accessible analogous climate space. The limited incorporation of non-equilibrium distributions into analyses, in part, is caused by the fact that no available software provides an intuitive or accessible way for researchers to quantify and incorporate non-equilibrium conditions into statistical tests of niche similarity.…”
Section: Introductionmentioning
confidence: 99%